Order Plecoptera - Avelino Capistrano, Fernanda; Pessacq, Pablo; Silva Barbosa, Leandro
Plecoptera is a small neopteran order that probablyemerged in the Upper Carboniferous (Grimaldi & Engel,2005; Bethoux et al., 2011). The order is distributed acrossall continents except Antarctica and has about 4,000species in 16 families (Fochetti & Tierno-de-Figueroa,2008). In the Neotropical region, there are 542 describedspecies (DeWalt et al., 2017) distributed in 6 families and48 endemic genera (except for Anacroneuria which is alsoreported in the Nearctic Region; Stark et al., 2009; Vera,2009; McCulloch et al., 2016). Adults are weak flyers andare found in riparian vegetation, typically at high elevations(up to 3,800e4,200 m) (Roback, 1980). However, theyalso occur at low elevations <100 m (e.g., Anacroneuriasp., Avelino-Capistrano, 2014) and even at sea level(Klapopteryx kuscheli IlliesdPessacq, pers. obs.). Theycan be easily found on substrates such as rocks, bryophytes,and litter in low-orders rivers with clean and flowingwater. Most Plecoptera nymphs are very sensitive toenvironmental pollution (exceptions include Anacroneuria;Avelino-Capistrano, 2014) and are often used in freshwatermonitoring programs (Callisto et al., 2001; Buss et al.,2002). However, much of those studies are based onfamily-level analyses (e.g., Junqueira & Campos, 1998;Miserendino & Pizzolo´n, 1999), in part because of the highdiversity and lack of adequate keys to identify stoneflies atlower taxonomic levels. Some authors have associatednymphs with adults by rearing methods (e.g., Ribeiro,2004; Ribeiro & Raphael, 2005; Pessacq & Omad, 2012),although in recent years, molecular tools have been successfullyused for this purpose (e.g., Mynott et al., 2011;Tierno-de-Figueroa et al., 2011; Avelino-Capistrano et al.,2014, 2015). Keys to Neotropical nymphs have beendeveloped by many authors (e.g., Benedetto, 1974;Romero, 2001), although the keys of Stark et al. (2009) arethe most comprehensive. This chapter is based in part onthis last work, with the addition of photographs, drawings,and the recently described ...